Pengembalian Utang untuk Modal Usaha Perternakan yang Bangkrut Persfektif Abdul Qadir Syaibah al-Hamd: Studi Kasus Desa Bandar Klippa Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Mutia Nalsa Hardanti; Rahmat Hidayat (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to analyze the practice of debt repayment for livestock business capital that has gone bankrupt, taking into account the perspective of Abdul Qadir Syaibah al-Hamd. Through a case study in Bandar Klippa Village, Percut Sei Tuan District, Deli Serdang Regency, it is hoped that a deep understanding can be obtained regarding the implementation of Islamic legal principles in real situations. This type of research is field research. The approach used in this research is a qualitative approach based on case studies. The natural data sources discussed in this research are divided into two, namely primary data sources and secondary data sources as follows: (1) Primary data obtained through interviews (2) Secondary data is data that is already available and can be obtained by researchers by reading, viewing or listening to books, articles. According to the Islamic Fiqhul book, Syarb Bulugh al-Maram Min jam' Adillatil Ahkam, debt is permitted. However, the person who owes it must really intend to repay the debt, because if they have assets but are reluctant to pay them, then this is injustice towards the person who owes it. The meaning of injustice in the above hadith is sin. Borrowers must continue to pay their debts even if the business they run goes bankrupt. The following is how problem credit can be resolved in several ways, namely: Rescheduling, Requirements, and Restructuring.